Short sellers and corporate disclosure - CHEN, Xia (Institutional Knowledge at Singapore Management University, 2020)
We examine how short sellers affect corporate disclosures using a natural experiment. From May 2005 to July 2007, the SEC implemented a pilot program by randomly selecting one third of Russell 3000 stocks and removing the short sale price tests for these stocks (referred to as pilot firms), leading to lower short-selling constraint, without changing the requirement for other firms (referred to as control firms). We compare the change in corporate disclosures between the pilot firms and the control firms during this period. We find that compared to the control firms, the pilot firms are more likely to issue good news management forecasts without changing the issuance of bad news forecasts. We also find that the decrease in short-selling constraint for the pilot firms (1) leads to an increased likelihood of bundling bad news forecasts with good news earnings announcements, and (2) does not lead to an increase in the optimistic bias in management forecasts. Overall, our evidence suggests that the reduction in short-selling constraint motivates managers to disclose good news in a more timely fashion.